Comparison times are longer for hedonic than for intensity judgements of taste stimuli - Veldhuizen, Maria G.; Vessaz, Melina N.; Kroeze, Jan H.A. (Physiology & behavior, 2005)
Response times of intensity and hedonic comparisons were determined in a within-subjects experimental design. Forced-choice paired comparisons of orange lemonades with various concentrations of added quinine sulfate were made by 48 subjects. Depending on experimental condition, the subjects had to focus either on intensity or on pleasantness and give their responses as fast as possible. The data showed shorter response times for intensity comparisons than for pleasantness comparisons. Although taste processing may be partially serial and partially parallel, the larger part of the response times and the differences between them may be due to cognitive processing.